Time trends in dietary Zn intake and occurrence of dietary Zn inadequacy among Chinese adults: data from the China Health and Nutrition Surveys between 2004 and 2011 - Lu LIU; Alida MELSE-BOONSTRA; Wen-Feng CONG; Mo LI; Fusuo ZHANG; Wopke VAN DER WERF; Tjeerd JAN STOMPH (Frontiers of Agricultural Science and Engineering)
Adequate dietary zinc intake remains a public health challenge in China. Also, there is a lack of information on the relationship between Zn intake and food consumption patterns across provinces and over time. In this study, data from the China Health and Nutrition Survey 2004–2011 (21,266 individuals) was used to explore associations between dietary Zn intake and sociodemographic factors. Zn intake per person declined from 11.1 mg·d−1 in 2004 to 9.89 mg·d−1 in 2011, with reduction in cereal consumption the greatest contributor to this. However, the reduction resulting from the lower cereal consumption was only partly compensated by an increase in consumption of Zn-rich foods. The percentage of the study population with inadequate Zn intake increased from 23% in 2004 to 37% in 2011. While Zn intake was positively associated with income levels in each survey year, the time trend for all income levels was a gradually reducing Zn intake. In all years, males had an average higher dietary Zn intake, whereas no significant difference was found between living areas. In conclusion, this study shows that dietary Zn inadequacy was high and has increased over the studied period. Remediation could be sought by shifting dietary patterns toward more Zn-dense food or by enhancing Zn concentration through biofortification.